Design of a Hybid Energy Metering System with an Alarm. - Kakuru Isaac (2023)
This report aims at proposing a system that reduces power loss and power theft due to the illegal activities. In this report, the prepaid power is monitored using a GSM module and is utilized so that the consumer can be persistently be educated on the energy utilization and if the sum of the energized achieves the base worth, it alanns the consumer to add more units. The major aim of this report is to lessen the long lines at power charging counters and to disconnect or remove the power automatically if the units get done, hence need to recharge. The system was designed around two modules, the hardware and the software modules The hardware module consists of ADE7755 used to generate the consumption pulses that are measured and recorded by Atmega328P. Atmega2560 was used to manage the unit consumption; control and monitor the activities of the meter. SIM900 was used to achieve the SMS recharging and communication capability. The server consists of Atmega328Pand SIM900 for communication. It is interfaced serially with the PC used for the Application Platform. The software module consists of the Application Platform especially for token generation and Database. The SMS Command format for recharging of the meter was also developed using GSM which is a cell system which implies that the cellular telephones unite with it via looking for cells in the prompt region in the neighboring cells to maintain a strategic distance from contortion in signs with the phone. The GSM-based Energy Metering System developed worked satisfactorily. It is reliable and efficient for use by the supply authority and the consumers